SOME ASPECTS OF THE THEORY OF WAVELETS - Núñez Ramírez, Luis Miguel (2010)
The aim of this paper is to briefly discuss some strategies that have been developed for the construction of trigonometric polynomial m0 under certain conditions. Also show the relationship between the function scale ϕ, the wavelet and the trigonometric polynomial m0. Therefore, the Multiresolution Analysis (AMR) plays a vital role in the construction of orthonormal bases of wavelets. Among the new techniques used, one of the most important is the theory of frames that have a direct relationship with the wavelets analysis.